Perancangan Aplikasi Poin Penjualan Manajemen Sistem Handayani Bakery & Cake Berbasis Web - Joko Habib Kaidafi; Hari Purwanto; Hari Mantik; Muryan Awaludin (Fakultas Ilmu Komputer & Desain, 2026)
Handayani Bakery & Cake is a small and medium enterprise (UKM) operating in the food industry with a focus on making and selling bread and cake products. However, in daily operations, we still use a manually documented system in terms of recording sales reports, accuracy of transaction data, and stock management which is done manually, which at any time can cause errors in recording and calculations. This research aims to build a system that is integrated with computers, namely a sales point system, so that managing sales data reports can be more effective, efficient and also accurate. The Point of Sales application uses the Laravel framework PHP programming language. The application development step begins with collecting the required data from interviewing and observing the existing process flow, creating a design plan, programming (coding) and system testing. The results of the research carried out by this system run well, it can document sales report data more efficiently, effectively and accurately.